Odpowiedź :
x = 1
a)x(x+2)+1=(x+1)(x+1)
x(kwadrat) +2x +1= x(kwadrat) +1
1(kwadrat) + 2*1 + 1 = 1(kwadrat) +1
1 + 2 + 1 = 1 + 1
4= 2
równość nie jest prawdziwa
b)(x+5)(x+5)=(x-5)(x-5)+20x
x(kwadrat) + 24 = x(kwadrat) -5x - 5x + 25 + 20x
1(kwadrat) + 24 = 1(kwadrat) + 10*1 + 25
1 + 25 = 1 + 10 +25
26 = 36
równość nie jest prawdziwa
a)x(x+2)+1=(x+1)(x+1)
x(kwadrat) +2x +1= x(kwadrat) +1
1(kwadrat) + 2*1 + 1 = 1(kwadrat) +1
1 + 2 + 1 = 1 + 1
4= 2
równość nie jest prawdziwa
b)(x+5)(x+5)=(x-5)(x-5)+20x
x(kwadrat) + 24 = x(kwadrat) -5x - 5x + 25 + 20x
1(kwadrat) + 24 = 1(kwadrat) + 10*1 + 25
1 + 25 = 1 + 10 +25
26 = 36
równość nie jest prawdziwa
a) 1(1+2)+1 = (1+1)(1+1)
1(3+1) =2X2
4=4
b)(1+5)(1+5)=(1-5)(1-5)+20X1
6x6 =-4x-4 +20
36=-16+20
36=4
1(3+1) =2X2
4=4
b)(1+5)(1+5)=(1-5)(1-5)+20X1
6x6 =-4x-4 +20
36=-16+20
36=4
a) x=4
x(x+2) +1=(x+1)(x+1)
4(4+2)+1=(4+1)(4+1)
16+8+1=16+4+4+1
25=25
b)x=2
(x+5)(x+5)=(x-5)(x-5)+20x
(2+5)(2+5)=(2-5)(2-5)+20×2
2+10+10+25=4-10-10-25+40
47=-9
x(x+2) +1=(x+1)(x+1)
4(4+2)+1=(4+1)(4+1)
16+8+1=16+4+4+1
25=25
b)x=2
(x+5)(x+5)=(x-5)(x-5)+20x
(2+5)(2+5)=(2-5)(2-5)+20×2
2+10+10+25=4-10-10-25+40
47=-9